Design And Synthesis Of An Azabicyclic Nucleoside Phosphoramidite For Oligonucleotide Antisense Constructs. (20th February 2020) - Salinas, Juan C.; Seth, Punit P.; Hanessian, Stephen
Abstract: We report the synthesis and biophysical evaluation of an azabicycle dinucleotide with restricted γ, β, and ε torsion angles, featuring the introduction of a piperidine ring that locks the conformation of the nucleoside into an RNA-type nucleic acid. The conceptual basis of the design is predicated upon the notion that the conformation of the phosphate group linking two RNA nucleotides can be approximated with an azabicyclic phosphoramidite which may also benefit from a unique stereoelectronic effect. Graphical Abstract: